High-yield-ratio ferrite-bainite dual-phase steel sheet and manufacturing method thereof
By regulating the chemical composition and process of ferrite bainite duplex steel thin plates, a microstructure containing ferrite, bainite and residual austenite is formed, which solves the problem of mechanical strength reduction after thinning of the steel plate, and achieves high yield and strength ratio and excellent forming performance.
Patent Information
- Application Number
- CN202411443850.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-02-28
AI Technical Summary
In the prior art, the mechanical strength of the steel plate is reduced after being thinned, and cannot withstand large loads, making it difficult to achieve the need for lightweight automobiles.
By regulating the chemical composition and ratio of ferrite bainite biphasic steel sheets and adopting specific manufacturing processes, including hot rolling, hood annealing, cold hard strip manufacturing and continuous annealing, a microstructure containing ferrite, bainite and residual austenite is formed.
On the premise of ensuring good forming properties, the tensile strength and strong plastic matching are improved, and the steel sheet with high yield and strength ratio can be uniformly deformed during the deformation process and effectively resist deformation, improving the overall performance of the material.
Smart Images

Figure CN119530665A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of automobile steel preparation, and in particular to a high yield ratio ferrite-bainite dual-phase steel sheet and a manufacturing method thereof. Background Art
[0002] In recent years, with the development of science and technology and the enhancement of people's environmental awareness, the new energy electric vehicle industry has flourished. While leading the global automobile development, it has also provided strong support for the low-carbon transformation of the automobile industry. Compared with traditional fuel vehicles, new energy electric vehicles pay more attention to cruising range, safety and service life. The existing technology usually uses the method of increasing the battery capacity of the battery pack to extend the cruising range of new energy electric vehicles. Due to the limited energy density of the battery, while increasing the battery capacity, the weight of the battery pack will also increase, resulting in the weight of new energy electric vehicles being greater than that of fuel vehicles of the same level. Taking a compact SUV as an example, the weight of a fuel vehicle is about 1.4 tons, while the weight of a new energy electric vehicle exceeds 1.7 tons. Among them, the weight of the best-selling new energy electric vehicles on the market is mainly concentrated in 2.2-2.4 tons, which is 300-500kg heavier than the fuel vehicles of the same level. The overweight body will not only shorten the service life of new energy electric vehicles, but also increase fuel consumption, affect the handling performance and induce safety hazards. New energy electric vehicles are more urgently in need of lightweighting than fuel vehicles.
[0003] Automobile lightweighting refers to reducing the overall weight of the automobile from the aspects of structure, materials and processing technology, while the automobile meets the basic performance requirements, safety requirements and cost control requirements. At present, the main ways to achieve automobile lightweighting include: 1. Optimizing the structure of components to make the components thin-walled, hollow, miniaturized or composite; 2. Using new materials, such as high-strength steel, aluminum, magnesium alloys and some non-metallic materials; 3. Improving processing technology, mainly including improving forming technology and connection technology.
[0004] Existing technologies usually use thinned high-strength steel to achieve lightweighting of automobiles. The thinned steel plate has better formability, but the mechanical strength will decrease as the thickness of the steel plate decreases, and it cannot withstand large loads. Summary of the invention
[0005] In order to solve the technical problem that the mechanical strength of the steel plate decreases after thinning, the present invention provides a high yield ratio ferrite-bainite dual-phase steel sheet and a manufacturing method thereof. By adjusting the chemical composition and proportion of the ferrite-bainite dual-phase steel sheet, the tensile strength and strength-plastic matching are improved while ensuring good formability of the ferrite-bainite dual-phase steel sheet.
[0006] In a first aspect, the present invention provides a high yield ratio ferrite bainite dual-phase steel sheet, wherein the high yield ratio ferrite bainite dual-phase steel sheet comprises the following chemical components, in percentage by mass: C 0.19%-0.24%, Si 1.1%-1.4%, Mn2.0%-2.5%, Nb 0.04%-0.07%, Cr 0.4%-0.6%, Alt 0.7%-0.9%, P≤0.005%, S≤0.003%, N≤0.0035%, O≤0.005%, and the balance is Fe and unavoidable impurities; The thickness of the high yield ratio ferrite bainite dual-phase steel sheet is 0.8-2.5mm, the yield ratio is 0.8-0.9, the tensile strength is greater than 1200MPa, the elongation after fracture is greater than 17%, the hole expansion rate is greater than 30%, and the strength-plasticity product is greater than 21GPa·%.
[0007] Furthermore, in terms of mass percentage, the chemical composition of the high yield ratio ferrite-bainite dual-phase steel sheet satisfies the following relationship: 1.8%≤Alt+Si≤2.2%. The Al element can replace the Si element to play a solid solution strengthening role, and is also beneficial to the formation of ferrite, while improving the surface quality. However, too high an Al content not only increases the difficulty of continuous casting, thereby increasing production costs and reducing efficiency; it also reduces strength. Therefore, the present invention controls the two elements to 1.8%≤Alt+Si≤2.2%.
[0008] Furthermore, the microstructure of the high yield ratio ferrite-bainite dual-phase steel sheet includes ferrite and bainite, wherein the volume percentage of ferrite is 30%-45%, and the volume percentage of bainite is 40%-50%. The present invention balances the strength-ductility matching of the steel and the excellent forming properties such as hole expansion by limiting the volume percentages of ferrite and bainite.
[0009] Furthermore, the microstructure of the high yield ratio ferrite-bainite dual-phase steel sheet also includes retained austenite, the volume percentage of the retained austenite is 12%-20%, and the retained austenite is distributed along the interface between ferrite and ferrite and / or between ferrite and bainite. The retained austenite distributed along the interface can improve the collision absorption performance of the steel and improve the strength and toughness of the steel.
[0010] In a second aspect, the present invention further provides a method for manufacturing a high yield ratio ferrite-bainite dual-phase steel sheet as described in any one of the above items, comprising the following steps: Step 1: manufacturing of hot-rolled steel coils, heating the steel billet to the soaking temperature and then keeping it warm, then rolling, two-stage cooling and coiling are performed in sequence to obtain hot-rolled steel coils with a thickness of 2.6-5.5 mm; Step 2: manufacturing of hood annealed coils, hood annealing the hot rolled steel coils to obtain hood annealed coils; Step 3: Manufacturing of cold-hardened steel strip, pickling the bell-annealed coil and then cold rolling to obtain cold-hardened steel strip with a thickness of 0.8-2.5 mm; Step 4: Manufacturing of continuous annealing steel coils, rapidly heating the cold hardened strip to the annealing temperature for annealing treatment, then rapidly cooling it to the over-aging temperature for over-aging treatment, and cooling it again after the over-aging treatment is completed.
[0011] Furthermore, in step one, the absorptive temperature is 1220-1260°C, and the holding time is 35-45min; during the rolling process, the starting rolling temperature is 1160°C±20°C, and the final rolling temperature is 840°C±15°C; the first stage of the two-stage cooling adopts an air cooling waiting mode, and the second stage of cooling adopts an ultra-fast water cooling mode, and the final cooling temperature of the second stage of cooling is 540°C±20°C.
[0012] Furthermore, the final cooling temperature of the air-cooling waiting mode is 700-730°C; the cooling rate of the ultra-fast water-cooling mode is >50°C / s.
[0013] Furthermore, in step 2, the hood annealing temperature is 630-650° C. and the hood annealing time is 7-8 hours, so as to ensure that the alloy elements in the steel are fully diffused and the structure of the steel after hot rolling is homogenized.
[0014] Furthermore, in step three, the cumulative reduction rate of cold rolling is greater than 55%. The structure after the cover is fully broken and more distortion energy such as dislocations can be accumulated. In the subsequent annealing and recrystallization process, the recrystallized grains are finer and more uniform, and a part of the dislocations can be retained in the grains, which is beneficial to improve the yield strength of the steel, that is, it is beneficial to improve the yield strength ratio. When microcracks are generated during the stretching or hole expansion deformation process, the fine grains can effectively increase the number of grain boundaries, and the high-density dislocations can increase the difficulty of crack propagation, thereby optimizing its strength, plasticity and formability.
[0015] Furthermore, in step 4, the heating rate of rapid heating is greater than 80°C / s; the annealing temperature is 830-850°C, and the annealing time is 30-60s; the cooling rate of rapid cooling is greater than 45°C / s; the over-aging temperature is 320°C±15°C, and the over-aging time is 300-360s; the cooling rate of re-cooling is 15-20°C / s, and the target temperature of re-cooling is ≤160°C.
[0016] The beneficial effects of the present invention are: The present invention provides a high yield ratio ferrite-bainite dual-phase steel sheet and a manufacturing method thereof. The microstructure obtained by adjusting the chemical composition and proportion of the ferrite-bainite dual-phase steel sheet and preparing it through a reasonable process includes ferrite, bainite and retained austenite. Different from the micropore growth aggregation fracture of ferrite-martensite dual-phase steel, the high yield ratio ferrite-bainite dual-phase steel prepared by the present invention has a volume percentage of 30%-45% ferrite, which can make it deform uniformly in the initial stage of deformation during the stretching and hole expansion deformation process; the volume percentage of 40%-50% bainite as a hard phase structure can effectively resist deformation; and the volume percentage of 12%-20% of the retained austenite produces a "TRIP effect", which generates expansion force in the surrounding ferrite and bainite structures through volume expansion, thereby releasing and relaxing the local stress concentration. Under the three-phase coordinated deformation as described above, the tensile strength and strength-plasticity matching of the ferrite-bainite dual-phase steel sheet are improved while ensuring that the ferrite-bainite dual-phase steel sheet has a certain elongation after fracture and hole expansion rate. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0018] Figure 1 1 is the engineering stress-engineering strain curve of the high yield ratio ferrite-bainite dual-phase steel sheet prepared in Example 1.
[0019] Figure 2 3 is a microstructure diagram of a high yield ratio ferrite-bainite dual-phase steel sheet prepared in Example 1.
[0020] Figure 3 This is a bright field TEM morphology of retained austenite in the high yield ratio ferrite-bainite dual-phase steel sheet prepared in Example 1.
[0021] Figure 4 This is a dark field TEM morphology of retained austenite in a high yield ratio ferrite-bainite dual-phase steel sheet prepared in Example 1.
[0022] Figure 5 yes Figure 3 The diffraction pattern of retained austenite marked by the middle circle. DETAILED DESCRIPTION
[0023] In order to enable those skilled in the art to better understand the technical solutions in the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0024] Embodiment 1-6 provides a method for manufacturing a high yield ratio ferrite-bainite dual-phase steel sheet, comprising the following steps: Step 1: Manufacturing of hot-rolled steel coils. The steel billet is heated to 1220-1260°C and then kept warm for 35-45 minutes, and then rolled. During the rolling process, the starting rolling temperature is 1160°C±20°C, and the final rolling temperature is 840°C±15°C. After rolling, two-stage cooling is performed. The first stage of cooling adopts an air cooling waiting mode, and the final cooling temperature of the air cooling waiting mode is 700-730°C. The second stage of cooling adopts an ultra-fast water cooling mode, and is cooled to 540°C±20°C at a cooling rate of >50°C / s for coiling to obtain a hot-rolled steel coil with a thickness of 2.6-5.5mm.
[0025] Step 2: manufacturing of hood annealing coils, placing the hot rolled steel coils in a hood annealing furnace for hood annealing, controlling the hood annealing temperature to be 630-650° C., and the hood annealing time to be 7-8 hours, to obtain hood annealing coils.
[0026] Step 3: Manufacturing of cold-hardened strip steel: pickling the hood annealed coil and then cold rolling it, with the cumulative reduction rate of cold rolling being greater than 55%, to obtain a cold-hardened strip steel with a thickness of 0.8-2.5 mm.
[0027] Step 4: Manufacturing of continuous annealing steel coils, rapidly heating the cold hardened strip to 830-850℃ at a heating rate of >80℃ / s for annealing for 30-60s, then rapidly cooling to 320℃±15℃ at a cooling rate of >45℃ / s for over-aging for 300-360s, and cooling again to ≤160℃ at a cooling rate of 15-20℃ / s after the over-aging treatment to obtain a high yield ratio ferrite bainite dual-phase steel sheet.
[0028] In Examples 1-6, the chemical composition and mass percentage of the steel billet are shown in Table 1, and the specific process parameters of steps 1 to 4 are shown in Table 2 and Table 3, respectively.
[0029] Table 1 Chemical composition and mass percentage of the steel billets in Examples 1-6
[0030] Table 2 Specific process parameters of step 1 and step 2 in Examples 1-6
[0031] Table 3 Specific process parameters of step 3 and step 4 in Examples 1-6
[0032] Samples were taken from the annealed steel plate and A was prepared according to GB / T 228.1-2021 "Tensile test of metallic materials - Part 1: Test method at room temperature" 50 The tensile test specimens were tested on a Zwick / Roell Z100 tensile testing machine for yield strength, tensile strength and elongation (A 50 ) to detect and calculate the yield strength ratio and strength-ductility product; according to GB / T 15825.4-2008 "Metallic Sheet Formability and Test Methods Part 4: Hole Expansion Test" standard, (150×150) mm samples were prepared, holes were made by drilling, and then hole expansion experiments were carried out to detect the hole expansion rate. The microstructure morphology characteristics of the ferrite-bainite dual-phase steel were observed by Axio ScopeA1 optical microscope, and the image was statistically analyzed and analyzed by Image J software to obtain the volume fraction of the ferrite structure; the D / max2400 X-ray diffractometer (XRD) was used to qualitatively and quantitatively detect and analyze the retained austenite structure, and the calculation and analysis were carried out according to the method in the industry standard YB / T 5338-2019 "X-ray Diffractometer Method for Quantitative Determination of Austenite in Steel". The results of the mechanical properties test and the results of the microstructure test are shown in Table 4.
[0033] Table 4 Mechanical properties and volume percentage of each phase structure of high yield ratio ferrite-bainite dual-phase steel sheets of Examples 1-6
[0034] It can be seen from Table 4 that the high yield ratio ferrite bainite dual-phase steel sheet prepared in Examples 1-6 has a yield ratio of 0.8-0.9, a tensile strength>1200MPa, an elongation after fracture>17%, a hole expansion rate>30%, and a strength-ductility product>21GPa·%. The microstructure of the high yield ratio ferrite bainite dual-phase steel sheet prepared in Examples 1-6 includes ferrite, bainite and retained austenite, and the retained austenite is distributed along the interface between ferrite and ferrite, and between ferrite and bainite, wherein the volume percentage of ferrite is 30%-45%, the volume percentage of bainite is 40%-50%, and the volume percentage of retained austenite is>12%.
[0035] The engineering stress-engineering strain curve of the high yield ratio ferrite-bainite dual-phase steel sheet prepared in Example 1 is as follows: Figure 1 As shown. Figure 1It can be seen that there is an obvious yield feature during the stretching process, which is due to the presence of 13% retained austenite in the material, resulting in the TRIP effect during the stretching process. Its tensile strength reaches 1244MPa, the yield strength ratio is 0.833, and the elongation after fracture reaches 20.2%. It has excellent strength-plasticity matching, and the strength-plasticity product reaches 25.13GPa·%.
[0036] The microstructure of the high yield ratio ferrite-bainite dual-phase steel sheet prepared in Example 1 is shown in FIG. Figure 2 As shown. Figure 2 It can be seen that the microstructure of the high yield ratio ferrite-bainite dual-phase steel sheet prepared in Example 1 includes ferrite and bainite, wherein the volume percentage of ferrite is 41% obtained by statistics and analysis of the image using Image J software; the retained austenite structure is qualitatively and quantitatively detected and analyzed using a D / max2400 X-ray diffractometer (XRD), and the volume percentage of retained austenite is calculated and analyzed to be 13%; therefore, the volume percentage of bainite is approximately 46%.
[0037] The morphology of retained austenite was observed under a transmission electron microscope (H-800, Transmission Electron Microscopy, TEM). The bright field TEM morphology, dark field TEM morphology and diffraction pattern of retained austenite in the high yield ratio ferrite-bainite dual-phase steel sheet prepared in Example 1 are shown in Figures 1 and 2, 3 and 4, respectively. Figure 3-5 shown.
[0038] Although the present invention has been described in detail with reference to the accompanying drawings and in combination with the preferred embodiments, the present invention is not limited thereto. Without departing from the spirit and essence of the present invention, a person of ordinary skill in the art may make various equivalent modifications or substitutions to the embodiments of the present invention, and these modifications or substitutions shall be within the scope of the present invention. Any person of ordinary skill in the art may easily think of changes or substitutions within the technical scope disclosed by the present invention, and these shall be within the scope of protection of the present invention.
Claims
1. A high yield ratio ferrite-bainite dual-phase steel sheet, characterized in that: The high yield ratio ferrite bainite dual phase steel sheet includes the following chemical compositions in percentage by mass: C 0.19%-0.24%, Si 1.1%-1.4%, Mn 2.0%-2.5%, Nb 0.04%-0.07%, Cr 0.4%-0.6%, Alt 0.7%-0.9%, P≤0.005%, S≤0.003%, N≤0.0035%, O≤0.005%, and the balance is Fe and unavoidable impurities; The thickness of the high yield ratio ferrite bainite dual-phase steel sheet is 0.8-2.5mm, the yield ratio is 0.8-0.9, the tensile strength is greater than 1200MPa, the elongation after fracture is greater than 17%, the hole expansion rate is greater than 30%, and the strength-plasticity product is greater than 21GPa·%.
2. The high yield ratio ferrite-bainite dual-phase steel sheet according to claim 1, characterized in that: In terms of mass percentage, the chemical composition of the high yield ratio ferrite-bainite dual-phase steel sheet satisfies the following relationship: 1.8%≤Alt+Si≤2.2%.
3. The high yield ratio ferrite-bainite dual-phase steel sheet according to claim 1, characterized in that: The microstructure of the high yield ratio ferrite-bainite dual-phase steel sheet includes ferrite and bainite, wherein the volume percentage of ferrite is 30%-45%, and the volume percentage of bainite is 40%-50%.
4. The high yield ratio ferrite-bainite dual-phase steel sheet according to claim 3, characterized in that: The microstructure of the high yield ratio ferrite-bainite dual-phase steel sheet also includes retained austenite, the volume percentage of the retained austenite is 12%-20%, and the retained austenite is distributed along the interface between ferrite and ferrite and / or between ferrite and bainite.
5. A method for manufacturing a high yield ratio ferrite-bainite dual-phase steel sheet according to any one of claims 1 to 4, characterized in that: The steps include: Step 1: manufacturing of hot-rolled steel coils, heating the steel billet to the soaking temperature and then keeping it warm, then rolling, two-stage cooling and coiling are performed in sequence to obtain hot-rolled steel coils with a thickness of 2.6-5.5 mm; Step 2: manufacturing of hood annealed coils, hood annealing the hot rolled steel coils to obtain hood annealed coils; Step 3: Manufacturing of cold-hardened steel strip, pickling the hood annealed coil and then cold rolling to obtain cold-hardened steel strip with a thickness of 0.8-2.5 mm; Step 4: Manufacturing of continuous annealing steel coils, rapidly heating the cold hardened strip to the annealing temperature for annealing treatment, then rapidly cooling it to the over-aging temperature for over-aging treatment, and cooling it again after the over-aging treatment is completed.
6. The manufacturing method according to claim 5, characterized in that: In step one, the absorptive temperature is 1220-1260°C, and the holding time is 35-45min; during the rolling process, the starting rolling temperature is 1160°C±20°C, and the final rolling temperature is 840°C±15°C; the first stage of the two-stage cooling adopts the air cooling waiting mode, and the second stage of cooling adopts the ultra-fast water cooling mode, and the final cooling temperature of the second stage of cooling is 540°C±20°C.
7. The manufacturing method according to claim 6, characterized in that: The final cooling temperature of the air-cooling waiting mode is 700-730℃; the cooling rate of the ultra-fast water-cooling mode is >50℃ / s.
8. The manufacturing method according to claim 5, characterized in that: In step 2, the hood annealing temperature is 630-650° C., and the hood annealing time is 7-8 hours.
9. The manufacturing method according to claim 5, characterized in that: In step 3, the cumulative reduction rate of cold rolling is greater than 55%.
10. The manufacturing method according to claim 5, characterized in that: In step 4, the heating rate of rapid heating is greater than 80°C / s; the annealing temperature is 830-850°C, and the annealing time is 30-60s; the cooling rate of rapid cooling is greater than 45°C / s; the over-aging temperature is 320°C±15°C, and the over-aging time is 300-360s; the cooling rate of re-cooling is 15-20°C / s, and the target temperature of re-cooling is ≤160°C.